2020
DOI: 10.1186/s12885-020-06955-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of surgical margins with local recurrence in patients undergoing breast-conserving surgery after neoadjuvant chemotherapy

Abstract: Background: The aim of the current study was to report a single-institution experience using breast-conserving surgery after neoadjuvant chemotherapy (NACT), focusing on the association between microscopic resection margin status and locoregional recurrence (LRR). Methods: Our institutional prospectively maintained database was reviewed to identify patients who were treated with NACT between January 2008 and April 2018. Results: Among the main partial mastectomy specimens available for analysis (n = 161), 28 h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…The MarginProbe device, which uses radiofrequency spectroscopy, has shown a trend towards reduction in re-excision rates for positive margins after NAC (31% vs. 6%) [20]. In a review from the American Society of Breast Surgeons registry, NST was the highest-ranked actionable factor associated with fewer reoperations for positive margins, a finding corroborated by several other studies [13, 21, 22].…”
Section: Bcs and Margins After Nstmentioning
confidence: 65%
See 2 more Smart Citations
“…The MarginProbe device, which uses radiofrequency spectroscopy, has shown a trend towards reduction in re-excision rates for positive margins after NAC (31% vs. 6%) [20]. In a review from the American Society of Breast Surgeons registry, NST was the highest-ranked actionable factor associated with fewer reoperations for positive margins, a finding corroborated by several other studies [13, 21, 22].…”
Section: Bcs and Margins After Nstmentioning
confidence: 65%
“…BCS, complete resection of the tumor with negative margins with adjuvant radiotherapy is equivalent to mastectomy after NST in terms of disease-free survival (DFS) and OS [7, 11-13].…”
Section: Bcs and Margins After Nstmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no association between local recurrence and margin distance in lumpectomy resection specimens [ 25 ]. However, in our study, a higher rate of recurrence was found in patients who had clear resection margins of lumpectomy specimens (i.e., 75%) (8/24).…”
Section: Discussionmentioning
confidence: 99%
“…Few other studies have assessed the effect of margin width on prognosis in patients treated with BCS-NAC. Rouzier et al [ 40 ] found that margins <2 mm were associated with increased local recurrence ( p = 0.04); conversely, other authors reported no associations between LRFS and margin distances [ 22 , 41 , 42 , 43 , 44 ]. A limitation of this and similar studies for the assessment of the width of excision margins is represented by the pattern of tumor regression after NAC (concentric vs. scattered) because this is not often reported in imaging examination, although it represents a fundamental parameter to perform a “ no ink on tumor ” glandular resection, using the yT size as surgical target.…”
Section: Discussionmentioning
confidence: 99%